REGULATORY AND TRANSPORT PROTEINS OF BLOOD SERUM AND FOLLICULAR FLUID IN PREDICTION OF EFFICIENCY OF THE PROGRAMS OF IN VITRO FERTILIZATION IN WOMEN WITH ADENOMYOSIS - Лихачева, Виктория Васильевна; Баженова, Людмила Григорьевна; Зорина, Раиса Михайловна; Маркдорф, Аркадий Геннадьевич; Чирикова, Тамара Семеновна; Шрамко, Светлана Владимировна; Филимонов, Сергей Николаевич (Medicine in Kuzbass, 2017)
Research objective: Study of the content as well as the effect on the outcomes of in vitro fertilization (IVF) programs of some regulatory and transport proteins: (alfa-2-macroglobulin (α2-МG), alfa-1-antitrypsin (α1-АТ), pregnancy associated alfa-2-glycoprotein (PAG), lactoferrin (LF), and albumin (ALB) in blood serum and follicular fluid in women with adenomyosis and tubal factor of infertility.Materials and methods. The study included 89 patients, among them in 31 women the cause of infertility was adenomyosis (as a result of IVF, 12 patients got pregnant and 19 did not), and 58 patients with tubal infertility (24 patients got pregnant and 34 did not). The content of alfa-2-macroglobulin (α2-MG), alfa-1-antitrypsin (α1-АТ) and pregnancy associated alfa-2-glycoprotein (PAG), lactoferrin (LF) was determined by the quantitative rocket ummunoelectrophoresis method with the application of research test systems developed on the basis of research laboratory (RL) of immunology at Novokuznetsk State Institute for Further Training of Physicians. The concentration of albumin was determined by biochemistry methods (with bromcresol green).Results. The research revealed that serum levels of alfa-2-macroglobulin, alfa-1-antitrypsin, pregnancy associated globulin, lactoferrin and albumin in women with adenomyosis generally over the group did not reliably differ from such indexes in women with tubal infertility. In the group of women with adenomyosis the low level of alfa-2-macroglobulin (less than 1.75 g/L) and alfa-1-antitrypsin (less than 1.9 g/L) in blood serum was associated with negative IVF program outcome. In tubal infertility negative outcome of IVF program was registered at the reduction in the blood serum albumin level below 41.5 g/L.Conclusion: The revealed changes, namely the α2-MG level below 1.75 g/L and α1-AT below 1.9 g/L in the infertile patients with adenomyosis, as well as the serum albumin level below 41.5 g/L in women with tubal infertility can be considered as predictors of the negative outcome of IVF programs. When these results are obtained, it is expedient to solve the problem of delayed transfer of embryos for the purpose of additional immunomodulatory therapy in the framework of preimplantation preparation in IVF programs.
Keywords: IVF; infertility; alfa-2-macroglobulin; alfa-1-antitrypsin; albumin; adenomyosis